Clinical Significance of Serum Albumin and Implications of FcRn Inhibitor Treatment in IgG-Mediated Autoimmune Disorders - Ward, E. Sally; Gelinas, Deborah; Dreesen, Erwin; Van Santbergen, Jolien; Andersen, Jan Terje; Silvestri, Nicholas J.; Kiss, Joseph E.; Sleep, Darrell; Rader, Daniel J.; Kastelein, John J. P.; Louagie, Els; Vidarsson, Gestur; et al. (Frontiers in Immunology, 2022)
Serum albumin (SA), the most abundant soluble protein in the body, maintains plasma oncotic pressure and regulates the distribution of vascular fluid and has a range of other important functions. The goals of this review are to expand clinical knowledge regarding the functions of SA, elucidate effects of dysregulated SA concentration, and discuss the clinical relevance of hypoalbuminemia resulting from various diseases. We discuss potential repercussions of SA dysregulation on cholesterol levels, liver function, and other processes that rely on its homeostasis, as decreased SA concentration has been shown to be associated with increased risk for cardiovascular disease, hyperlipidemia, and mortality. We describe the anti-inflammatory and antioxidant properties of SA, as well as its ability to bind and transport a plethora of endogenous and exogenous molecules. SA is the primary serum protein involved in binding and transport of drugs and as such has the potential to affect, or be affected by, certain medications. Of current relevance are antibody-based inhibitors of the neonatal Fc receptor (FcRn), several of which are under clinical development to treat immunoglobulin G (IgG)-mediated autoimmune disorders; some have been shown to decrease SA concentration. FcRn acts as a homeostatic regulator of SA by rescuing it, as well as IgG, from intracellular degradation via a common cellular recycling mechanism. Greater clinical understanding of the multifunctional nature of SA and the potential clinical impact of decreased SA are needed; in particular, the potential for certain treatments to reduce SA concentration, which may affect efficacy and toxicity of medications and disease progression.